Survival After Ventricular Fibrillation Cardiac Arrest in the Sao Paulo Metropolitan Subway System: First Successful Targeted Automated External Defibrillator (AED) Program in Latin America. Issue 10 (October 2015) - Gianotto‐Oliveira, Renan; Gonzalez, Maria Margarita; Vianna, Caio Brito; Monteiro Alves, Maurício; Timerman, Sergio; Kalil Filho, Roberto; Kern, Karl B.
Abstract : Background: Targeted automated external defibrillator (AED) programs have improved survival rates among patients who have an out‐of‐hospital cardiac arrest (OHCA) in US airports, as well as European and Japanese railways. The Sao Paulo (Brazil) Metro subway carries 4.5 million people per day. A targeted AED program was begun in the Sao Paulo Metro with the objective to improve survival from cardiac arrest. Methods and Results: A prospective, longitudinal, observational study of all cardiac arrests in the Sao Paulo Metro was performed from September 2006 through November 2012. This study focused on cardiac arrest by ventricular arrhythmias, and the primary endpoint was survival to hospital discharge with minimal neurological impairment. A total of 62 patients had an initial cardiac rhythm of ventricular fibrillation. Because no data on cardiac arrest treatment or outcomes existed before beginning this project, the first 16 months of the implementation was used as the initial experience and compared with the subsequent 5 years of full operation. Return of spontaneous circulation was not different between the initial 16 months and the subsequent 5 years (6 of 8 [75%] vs. 39 of 54 [72%]; P =0.88). However, survival to discharge was significantly different once the full program was instituted (0 of 8 vs. 23 of 54 [43%]; P =0.001). Conclusions: Implementation of a targeted AED program in the Sao Paulo Metro subway system saved lives. A short interval between arrest and defibrillation was key for good long‐term, neurologically intact survival. These results support strategic expansion of targeted AED programs in other large Latin American cities.